Handbook of radiopharmaceutical controls - Noto, María Gracia; de Suárez, Amanda H. F. (Comisión Nacional de Energía Atómica; Argentina, 1980)
Fil: Noto, María Gracia Comisión Nacional de Energía Atómica; Argentina